Evaluation of the development of the posterior fossa in normal Chinese fetuses by using magnetic resonance imaging. Issue 16 (April 2020) - Ye, Jintang; Rong, Rong; Dou, Yanbin; Jiang, Jian; Wang, Xiaoying
Abstract : Abstract: The posterior fossa is an important brain structure containing the cerebellum, cerebral ventricle, and cistern. Early evaluation of the cerebellar structure and function may be valuable for early detection of fetal deformities. At present, no normal value for the fetal posterior fossa has been established yet. This study is aimed to investigate the development of the posterior fossa in normal Chinese fetuses by using magnetic resonance imaging (MRI). Pregnant women who need MRI scan were enrolled in our Hospital between January 2012 and December 2014. The fetal supero-inferior diameter (SID), anterio-posterior diameter (APD), cerebellar vermis area, cerebellar width (CW), cerebellar volume (CV), superior cerebellar cistern width, and cerebellomedullary cistern width were measured using MRI. Pearson's correlation analysis was used to detect the relationship between those parameters and gestational age. A regression analysis was performed for all parameters. A total of 92 participants were retrospectively enrolled finally. The results indicated SID, APD, cerebellar vermis area, CW, and CV were positively associated with gestational age, while no significant correlation was found between the superior cerebellar cistern width and cerebellomedullary cistern width and gestational age. Each equation was established. Our study demonstrated that MRI has the advantages over ultrasound imaging for prenatal evaluation of the fetal posterior fossa with multiple views. Normal value of the posterior fossa of Chinese fetuses was established in this study.